Infertility and cortisol: a systematic review - Karunyam, Bheena Vyshali; Abdul Karim, Abdul Kadir; Naina Mohamed, Isa; Ugusman, Azizah; Mohamed, Wael M. Y.; Faizal, Ahmad Mohd; Abu, Muhammad Azrai; Kumar, Jaya (Frontiers in Endocrinology, 2023)
Stress and infertility form a complex relationship. In line with this, various stress-related biological markers have been investigated in infertility. This systematic review was performed using PRISMA guidelines (i) to report whether cortisol is highly present in infertile patients compared to fertile control; (ii) to report whether there is any significant difference in the cortisol level in infertile subjects that conceive and those that didn’t at the end of assisted reproduction treatments. Original articles involving human (male and female) as subjects were extracted from four electronic databases, including the list of references from the published papers. Sixteen original full-length articles involving male (4), female (11), and both genders (1) were included. Findings from studies that compared the cortisol level between infertile and fertile subjects indicate that (i) Male: three studies reported elevated cortisol level in infertile patients and one found no significant difference; (ii) Female: four studies reported increased cortisol level in infertile subjects and three studies found no significant difference. Findings from studies that measured the cortisol level from infertile patients that conceived and those that didn’t indicate that (i) Male: one study reported no significant difference; (ii) Female: one study reported elevated cortisol in infertile patients that conceived, whereas two studies reported increased cortisol in infertile patients that was unable to conceive. Five studies found no significant difference between the groups. In the present review we only included the cortisol value that was measured prior to stimulation or IVF treatment or during natural or spontaneous cycles, despite this, there are still variations in the sampling period, assessment techniques and patients’ characteristics. Hence, at present, we are still unable to conclude that cortisol is significantly elevated in infertile patients. We warrant future studies to standardize the time of biological sample collection and other limitations that were addressed in the review to negate the unwanted influencing factors.